Patterns of co-administration and sequential administration of COVID-19 and influenza vaccinations: a US study using Adheris pharmacy dataset - Alon Yehoshua; Tianyan Hu; Taryn Pond; Jingyan Yang; Verna Welch; Constantina Boikos; Sen Deng; Hao Zheng; Poorva Sardana; Neha Agrawal; Manvi Sharma (Expert Review of Vaccines)
Background This study assessed monthly patterns of co-administration of COVID-19 and influenza vaccines at visit level and quantified the number and proportion of adults who received both vaccines on the same day or sequentially.Research design and methods This retrospective study utilized the Adheris pharmacy dataset and included adults aged ≥ 19 years with a record of ≥ 1 dose of COVID-19 or influenza vaccines between August 2022 and December 2023. Administration of both vaccines on the same day was defined as co-administration, and administration of vaccines within 1–180 days was referred to as sequential administration. Descriptive analyses were performed.Results Among 31.5 million visits with either COVID-19 or influenza vaccines, 5.8 million (18.5%) involved co-administration. Co-administration visits were higher between September and November compared to other months, rising to 1.5 million in October 2023. Among 7.9 million adults with both vaccines, 65.8% had same day administration, while 34.2% had sequential administration. 60.7% of adults with sequential administration received the vaccines within 1–30 days.Conclusions About one in five COVID-19 or influenza vaccinations involved co-administration. The majority of sequential administrations happened within 30 days, highlighting missed opportunities for co-administration. These findings suggest substantial potential to improve uptake of both vaccines through co-administration.